Chemerin/CMKLR1 Axis Promotes the Progression of Proliferative Diabetic Retinopathy - Lihui Wang; Ying Zhang; Yanan Guo; Wencui Ding; Ailing Chang; Jing Wei; Xinsheng Li; Hongxia Qian; Chonggui Zhu (International Journal of Endocrinology)
Background. Diabetic retinopathy (DR) is a prevalent microvascular complication of diabetes, and the levels of chemerin were associated with the severity of DR. However, there is no research on chemerin in the development of proliferative diabetic retinopathy (PDR). Therefore, our study aimed to explore the relationship between chemerin and PDR. Methods. The levels of chemerin/chemokine-like receptor (CMKLR1), proinflammatory cytokines, and vascular endothelial growth factor (VEGF) in 90 cases of PDR and nonproliferative diabetic retinopathy (NPDR) patients and in high glucose (HG) stimulated human retinal pigment epithelium cells (ARPE-19) were evaluated by ELISA. Moreover, chemerin was added into HG-induced ARPE-19 cells to assess its effect on proinflammatory cytokines and VEGF. Results. The levels of chemerin/CMKLR1 were higher in PDR patients than NPDR ones, and chemerin was positively correlated with CMKLR1 in PDR patients. Compared to NPDR, the secretions of proinflammatory cytokines and VEGF were increased in PDR patients and positively correlated with chemerin/CMKLR1. Additionally, chemerin activated CMKLR1 and aggravated HG-induced cell injury, inflammatory responses, and VEGF expressions in ARPE-19 cells. Conclusion. Our study demonstrated that chemerin/CMKLR1 axis aggravated the progression of PDR, which suggested that inhibition of chemerin might serve as a new therapeutic approach to treat PDR.